THE EFFECTIVENESS OF HEALTH EDUCATION AND MEDIA USING LOCAL LANGUAGE IN IMPROVING REPRODUCTIVE HEALTH KNOWLEDGE AMONG ADOLESCENTS (Proceedings of the International Conference on Public Health, 2024)
Health education and media have been identified as strategies to improve adolescents' reproductive health knowledge, but barriers can be influenced by cultural context, including language. This study aims to assess the effectiveness of health education and media using the local language in improving reproductive health knowledge among adolescents in Bhuana Giri Village, Karangasem. The research design is a quasi-experimental two-group pre-posttest design, and purposive sampling was used to select the samples. A total of 50 students aged 12 to 17 years participated in the study. The first group received health education and media in the local language on reproductive health topics, while the other group received the same topics in the national language. Data analysis used the Wilcoxon signed-rank test and Mann-Whitney test with a significant level of 0.05. The results showed that both interventions led to significant improvements in reproductive health knowledge. There was an effect of giving health education and media using the local language (p
Keywords: health education; media; local language; reproductive health; adolescents